2016
DOI: 10.1039/c5ra27035a
|View full text |Cite
|
Sign up to set email alerts
|

A new l-arabinose isomerase with copper ion tolerance is suitable for creating protein–inorganic hybrid nanoflowers with enhanced enzyme activity and stability

Abstract: Protein-inorganic hybrid nanoflowers were prepared using Cu 2+ , PBS buffer, and a copper ion tolerant L-arabinose isomerase that was derived from Paenibacillus polymyxa (PPAI). The expensive rare sugar L-ribulose or D-tagatose was prepared utilizing these nanoflowers with L-arabinose or D-galactose as the substrate, respectively. The PPAI hybrid nanoflowers showed better enzyme stabilities in both thermal and acidic conditions. Meanwhile, long term batch production was successful showing high stability using … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(6 citation statements)
references
References 30 publications
1
4
1
Order By: Relevance
“…On the other hand, an increase in BSA concentration promotes the number of nucleation sites, resulting in a slight decrease in the average size of NCs. In the present study, the influence of protein concentration on the morphology of the NCs shows a stark contrast with that in previous reports on hybrid nanoflowers fabricated in free solutions. , Without a solid platform, it was reported that a high protein concentration inhibited the “blooming” of the nanoflowers, and therefore, a closed arrangement of nanopetals was likely to occur. With the present inorganic platforms, the nanoflowers shape remains similar regardless of the protein concentration.…”
Section: Resultscontrasting
confidence: 99%
See 1 more Smart Citation
“…On the other hand, an increase in BSA concentration promotes the number of nucleation sites, resulting in a slight decrease in the average size of NCs. In the present study, the influence of protein concentration on the morphology of the NCs shows a stark contrast with that in previous reports on hybrid nanoflowers fabricated in free solutions. , Without a solid platform, it was reported that a high protein concentration inhibited the “blooming” of the nanoflowers, and therefore, a closed arrangement of nanopetals was likely to occur. With the present inorganic platforms, the nanoflowers shape remains similar regardless of the protein concentration.…”
Section: Resultscontrasting
confidence: 99%
“…Thus, P1 triggers a large number of NCs in the resultant flower-bed layer (PNC1) due to its large population of micropores, while those fabricated with P2 and P3 (PNC2 and PNC3, respectively) show a smaller number of NCs that is relatively proportional to their porosity. In addition, the facilitation of the inorganic platforms accelerated the self-assembly process from 72 h in previous studies , to 48 h in this work.…”
Section: Resultssupporting
confidence: 59%
“…Advantages of protein-inorganic hybrid biocatalysts for conversion of carbohydrates are mild synthesis conditions and high selectivity for desired products. 46,47 However, the requirement of pure enzymes for the synthesis of hybrid biocatalysts is a disadvantage. 47…”
Section: Production Of L-xylulosementioning
confidence: 99%
“…46,47 However, the requirement of pure enzymes for the synthesis of hybrid biocatalysts is a disadvantage. 47…”
Section: Production Of L-xylulosementioning
confidence: 99%
“…This circumstance can be prejudicial, since copper has been identified as an efficient inhibitor of the activity of a large variety of enzymes . In fact, in their attempt to create l ‐arabinose isomerase nanoflowers, Xu et al were forced to use a copper‐tolerant variant in order to avoid detrimental effects on the enzyme performance . Moreover, only few examples of nanoflowers have been reported combining phosphate salts and specific enzymes with further divalent cations (e.g., Ca 2+ , Co 2+ , Zn 2+ ) .…”
Section: Introductionmentioning
confidence: 99%